2022
DOI: 10.21203/rs.3.rs-1563674/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary fibers boost gut microbiota-produced B vitamin pool and alter host immune landscape

Abstract: Dietary fibers can alter microbial metabolic output in support of healthy immune function, however, the impact of distinct fiber sources and immunomodulatory effects beyond short-chain fatty acid production are underexplored. In an effort to discern the effects of diverse fibers on host immunity, we employed five distinct rodent diets with varying fiber content and source in specific-pathogen-free, gnotobiotic (containing a 14-member synthetic human gut microbiota), and germ-free mice. Broad-scale metabolomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To this point, Lubin et al demonstrated that restricting the microbiome to a pre‐weaning community halts immune development and increases susceptibility to Salmonella infection (Lubin et al , 2023), reflecting the need for a functionally balanced synthetic community to elicit normal immune development. As with other gnotobiotic models, the 14SM immune profiles typically represent an intermediate between GF and SPF colonization states in adulthood, potentially due to low diversity, low bacterial density and/or absence of specific immunogenic bacteria such as segmented fillamentous bacteria (Parrish et al , 2022b). Addition of new members may be a promising approach to refine these models, although it remains difficult to completely recapitulate SPF immune profiles (Afrizal et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this point, Lubin et al demonstrated that restricting the microbiome to a pre‐weaning community halts immune development and increases susceptibility to Salmonella infection (Lubin et al , 2023), reflecting the need for a functionally balanced synthetic community to elicit normal immune development. As with other gnotobiotic models, the 14SM immune profiles typically represent an intermediate between GF and SPF colonization states in adulthood, potentially due to low diversity, low bacterial density and/or absence of specific immunogenic bacteria such as segmented fillamentous bacteria (Parrish et al , 2022b). Addition of new members may be a promising approach to refine these models, although it remains difficult to completely recapitulate SPF immune profiles (Afrizal et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…All parental mice were maintained on the FR diet, which is a standard rodent chow (SAFE ® R04, Augy, France), until 2 weeks after the oral gavage. After this period, the parental mice designated as FF were switched to the custom FF chow, which is a modified version of Harlan TD.08810 diet and is manufactured by the same vendor as the FR diet, as previously reported (Parrish et al , 2022b). Mice were maintained on the FF diet for at least 20 days prior to setting breeding pairs and the respective diets were administered ad libitum for the remainder of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed compositions of the fiber-rich (FR) and fiber-free (FF) diets used in this study are as previously reported (Parrish et al , 2022c). Gnotobiotic FR mice were fed a standard rodent chow (SAFE®R04, Augy, France).…”
Section: Methodsmentioning
confidence: 99%
“…Gnotobiotic FR mice were fed a standard rodent chow (SAFE®R04, Augy, France). The FF diet is a modified version of Harlan TD.08810 diet, manufactured by the same vendor as the standard chow, as previously reported(Parrish et al , 2022b).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial DNA was extracted from fecal pellets by phenol-chloroform extraction, as previously described (Steimle et al , 2021). Total RNA was extracted from the host mesenteric lymph nodes, colonic tissue, or cecal contents at 3 DPI, as previously described (Grant et al , 2023; Parrish et al , 2022). RNA integrity was determined using an Agilent 2100 Bioanalyzer system and the RNA was stored at –80°C until further analysis.…”
Section: Methodsmentioning
confidence: 99%